Molecular medicine genomics to personalized healthcare - Trent, R.J (Elsevier/Academic Press, 2012)
Molecular Medicine is the application of genetic or DNA-based knowledge to the modern practice of medicine. Molecular Medicine, 4e, provides contemporary insights into how the genetic revolution is influencing medical thinking and practice. The new edition includes recent changes in personalized medicine, new growth in omics and direct-to-consumer DNA testing, while focusing on advances in the Human Genome project and implications of the advances in clinical medicine. Graduate students, researchers, clinicians and allied health professionals will appreciate the background history and clinical application of up-to-date molecular advances.